A New Measure of Reading Habit: Going Beyond Behavioral Frequency - Schmidt, Fabian T. C.; Retelsdorf, Jan (Frontiers in Psychology, 2016)
Reading habit is considered an important construct in reading research as it serves as a significant predictor of reading achievement. However, there is still no consensus on how to best measure reading habit. In recent research, it has mostly been measured as behavioral frequency; this approach neglects the fact that repeated behavior does not cover the broad content of habitual behavior—such as automaticity and the expression of one’s identity. In this study, we aimed to adapt a 10-item scale on the basis of the Self-Report Habit Index by Verplanken and Orbell (2003) that is comprehensive but still economical for measuring reading habit. It was tested by drawing on a sample of N = 1,418 upper secondary school students. The scale showed good psychometric properties and indicators for the internal and external validity and predicted reading achievement and decoding speed over and above reading frequency. The implications of an elaborated but still economical way of measuring reading habit are discussed giving new impetus on research on reading habit, challenging conventional approaches of traditional measures.